Inactivation of Aspergillus flavus spores by curcumin-mediated photosensitization - Temba, Benigni A.; Fletcher, M.T.; Fox, Glen P.; Harvey, Jagger J.W.; Sultanbawa, Y. (Elsevier, 2016)
Minimizing fungal infection is essential to the control of mycotoxin contamination of foods and feeds but many potential control methods are not without their own safety concerns for the consumers. Photodynamic inactivation is a novel light-based approach which offers a promising alternative to conventional methods for the control of mycotoxigenic fungi. This study describes the use of curcumin to inactivate spores of Aspergillus flavus, one of the major aflatoxin producing fungi in foods and feeds. Curcumin is a natural polyphenolic compound from the spice turmeric (Curcuma longa). In this study the plant has shown to be an effective photosensitiser when combined with visible light (420 nm). The experiment was conducted in in vitro and in vivo where A. flavus spores were treated with different photosensitiser concentration and light dose both in buffer solution and on maize kernels. Comparison of fungal load from treated and untreated samples was determined, and reductions of fungal spore counts of up to 3 log CFU ml−1 in suspension and 2 log CFU g−1 in maize kernels were obtained using optimal dye concentrations and light dose combinations. The results in this study indicate that curcumin-mediated photosensitization is a potentially effective method to decontaminate A. flavus spores in foods and feeds.